Our experience using tissue expansion in reconstructive surgery - Vanya Anastasova; Elena Krasteva; Petar Kiskinov; Karina Ivanova; Aleksandar Georgiev; Dimitar Dachev; Biser Ivanov; Elean Zanzov (Folia Medica)
Introduction: Expansion of tissues is a physiological phenomenon observed in processes such as pregnancy, breast growth, tumor development, and formation of seromas or hematomas. Over the last decade, there has been an increase in the number of patients with post-burn and post-traumatic defects and contractures. After Neumann introduced it in 1957, surgical treatment with tissue expanders has become an established method for managing major defects that do not have enough surrounding tissue to form a flap. This technique allows tissue defects to be covered with tissue that has similar color, thickness, and elasticity to the surrounding area. When combined with other plastic surgery methods, tissue expansion facilitates the coverage of large soft tissue defects of various etiologies with minimal formation of new scars and minimal donor site morbidity. Aim: Our study aimed to demonstrate the role of tissue expansion in reconstructive surgery, particularly in the treatment of soft tissue injuries in the scalp. Materials and methods: In this study we present ten cases treated for tissue defects using the expander technique. We used expanders of various shapes and sizes, with volumes ranging from 400 to 500 ml. Results: Reconstruction was deemed successful in 9 out of 10 patients. In one patient with scalp carcinoma, treatment was not completed due to rapidly progressing multiple metastatic lesions in parenchymal organs. The study observed particularly good results in six patients, good results in two patients, and satisfactory results in one patient. The total duration of treatment ranged from 1.5 to 2.5 months. Conclusion: Tissue expansion is an extremely suitable method for repairing the effects of thermal, mechanical, or combined injuries.